Case Report: Eyelid reconstruction using intact fish skin xenograft following periorbital necrotizing fasciitis - Shott, Molly; Wang, Diane; Nguyen, John (Frontiers in Ophthalmology, 2025)
Periorbital necrotizing fasciitis (NF) is a rare, vision-threatening soft tissue infection that requires rapid antimicrobial treatments to minimize devastating soft tissue destruction, and debridement of affected tissue results in extensive defects requiring various techniques of reconstruction. We herein describe a case of a 58-year-old male with periorbital NF who underwent eyelid repair with intact fish skin grafts. To our knowledge, this is the first case report of fish skin grafts being used in eyelid wound management after periorbital NF.